2011
DOI: 10.1159/000323319
|View full text |Cite
|
Sign up to set email alerts
|

Reflex High Risk HPV Testing in Atypical Squamous Cells, Cannot Exclude High Grade Intraepithelial Lesion: A Large Institution’s Experience with the Significance of This Often Ordered Test

Abstract: Objective: Cervical cytology specimens diagnosed with ASC-H consist of squamous cells with equivocal cytology for high-grade dysplastic lesions. We reviewed our cases of ASC-H with reflex HPV testing to evaluate this patient population. Study Design: We retrospectively identified patients with ASC-H in Pap smears over a 3-year period. Reflex high-risk (HR) HPV DNA testing was performed by request. Follow-up results and smear characteristics were evaluated. Results: HR HPV DNA testing was positive in 60 of 82 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
(68 reference statements)
2
14
0
Order By: Relevance
“…51 At least 1 study on hrHPV testing with ASC-H LBC results has come to similar conclusions. 52 Other studies have reported different findings. 26,53 The full significance of negative hrHPV test results in the face of significantly abnormal cytology findings, such as HSIL, remains controversial.…”
Section: Discussionmentioning
confidence: 96%
“…51 At least 1 study on hrHPV testing with ASC-H LBC results has come to similar conclusions. 52 Other studies have reported different findings. 26,53 The full significance of negative hrHPV test results in the face of significantly abnormal cytology findings, such as HSIL, remains controversial.…”
Section: Discussionmentioning
confidence: 96%
“…An overview of the study design, population, and test characteristics of the included studies is presented in Supporting Table 1 (see online supporting information). Eight reports had a prospective design, and 17 reports had a retrospective design . Eighteen studies included women with ASC‐H identified through primary screening, and 7 studies recruited subjects in colposcopy clinics to which women had been referred because of a prior cytological result of ASC‐H .…”
Section: Resultsmentioning
confidence: 99%
“…As an uncommon cytological interpretation, ASC‐H is reported infrequently, and the prevalence of Papanicolaou smears interpreted as ASC‐H varies significantly among laboratories with a mean reporting rate of 0.43% (5th‐95th percentiles, 0%‐2%) in the United States . The finding of ASC‐H is often associated with a high human papillomavirus (HPV)–positive rate (10th‐50th‐90th percentiles, 0%‐54%‐79%) and relatively high risks of underlying grade 2 cervical intraepithelial neoplasia or worse (CIN2+) and grade 3 cervical intraepithelial neoplasia or worse (CIN3+), which range from 13% to 66% and from 11% to 35%, respectively. In comparison, ASC‐US is a far more prevalent cytological category and has a lower likelihood of underlying CIN2 + (pooled average, 12%) or CIN3 + (pooled average, 7%) …”
Section: Introductionmentioning
confidence: 99%
“…7 HPV testing is now routinely ordered for many patients with ASC-H Pap test results, either as a routine cotest in women aged 30 years and older or as an elective reflex test after ASC-US or ASC-H findings. [8][9][10][11] The purpose of our study was to document the histopathologic and cytologic follow-up findings for a large group of patients with HPVnegative ASC-H results. The negative predictive value for hrHPV in most studies, based on short-term colposcopic and histopathologic follow-up examinations, has been in the range of 95% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although most studies have concluded that a negative hrHPV test result accompanying ASC-H offers high negative predictive value and a reasonable basis for considering triage to routine periodic screening, a few studies have disagreed. 10,11 Women with Pap interpretations of ASC-H and concurrent hrHPV negative test results remain an incompletely studied population with little published follow-up beyond short-term colposcopic findings. Data confirming a sufficiently high negative predictive value for hrHPV-negative ASC-H results would support adjusting initial recommendations for colposcopic referral of all women with ASC-H Pap results.…”
mentioning
confidence: 99%